Extracellular miRNAs: the mystery of their origin and function - Turchinovich, Andrey; Weiz, Ludmila; Burwinkel, Barbara (Trends in biochemical sciences, 2012)
Mature miRNAs are 19-24 nucleotide noncoding RNAs that post-transcriptionally regulate gene expression in living cells by mediating targeted hydrolysis and translation inhibition of mRNAs. In recent years, miRNAs have been detected in a variety of biological fluids as extracellular nuclease-resistant entities. Importantly, extracellular circulating miRNAs are aberrantly expressed in blood plasma or serum during the course of many diseases, including cancer, and are promising noninvasive biomarkers. However, the biological function of extracellular miRNAs remains questionable. In this article, we summarise the current theories regarding extracellular miRNA origin and function, and suggest that these miRNAs are mostly byproducts of cellular activity. Nevertheless, some extracellular miRNA species might also carry cell-cell signaling function.
Gesehen am 17.09.2018